A Mathematical Model That Semantically Analyzes Polysemantic Words - Elov Botir Boltayevich; Akhmedova Kholisa Ilkhomovna (Zien Journals, 2021)
The world experience of semantic analysis of polysemous words has been studied. The ways of formation of polysemantic words in Uzbek language are described. The differences between ambiguous and ambiguous words and the classification of polysemous words within word groups are given. An example of a polysemantic eye word is the architecture of semantic analysis. Based on the given architecture, a mathematical model that semantically analyzes polysemantic words is recommended. The result of this mathematical model is examined in context
Keywords: Polysemy; semantic analyzer; polysemous word; semantic analysis